A retrospective analysis on the correlation between hip pain, physical examination findings, and alpha angle on MR images. Issue 1 (December 2016) - Guler, Olcay; Isyar, Mehmet; Karataş, Dilek; Ormeci, Tugrul; Cerci, Halis; Mahirogulları, Mahir
Abstract Background We aimed to search whether alpha angle, a radiological clue used in the diagnosis of femoroacetabular impingement, is correlated with the presence of hip pain, internal rotation angle, and impingement test results on hip impingement patients (CAM type). Methods Medical records of 334 patients (156 women, 178 men) with an average age of 33.8 ± 8.4 (range 20–50) years were retrospectively studied for the alpha angle of the hip measured on magnetic resonance images (MRI). Hip pain and internal rotation angles as well as results of impingement tests were reviewed. Results Hip pain was reported more frequently on the right side (n  = 35, 10.5%) compared to the left side (n  = 22, 6.6%) (p  = 0.047). No difference was observed between the right and left sides regarding alpha angles (p  = 0.145), internal rotation angles (p  = 0.637), or positivity of impingement test (p  = 0.210). Internal rotation angles were significantly higher in cases without hip pain (p  < 0.001) and in patients with negative impingement test result (p  < 0.001). Internal rotation angle correlated positively with age and negatively with the alpha angle. Alpha angle was increased in cases that report pain, those with an internal rotation angle <20°, or cases with positive impingement test. The pain was more common, internal rotation angle was higher, and positivity for impingement was more frequent if the alpha angle was <55°. Patients with hip pain or positive impingement test or internal rotation angle <20° had increased alpha angles (p  < 0.001). Conclusions The pain, impingement test results, and internal rotation angle seem to be associated with alpha angle of the hip measured on MRI in hip impingement patients.